INTRAVENOUS MEDICATION ADMINISTRATION ERRORS AND THIS CAN ENDANGER THE LIVES OF PATIENTS - SALIH AL-ANI, OMAR ABDULWAHID (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Intravenous errors are one of the most frequent and common medical errors, but no direct causes found. The theory of human error is the most common expression of errors in hospitals, and this can endanger the lives of patients. This research study aims to identify the errors in the vein and try to find solutions to avoid those errors where the study conducted on a sample of hospitals in Baghdad. Methods: The study conducted to improve health quality in some hospitals. During the study period, a group of severe cases was detected, which based on intravenous infusions. Patients’ data and information were collected through five sources, examined and documented venous errors found and placed in a standard classification according to an incorrect dose and incorrect medication. The incorrect dose includes the following: Overdose, extra dose, underdose, wrong strength, and wrong form. Results: During the period of study, a total of 99 cases, among these cases, 52 incorrect medications include (drug-drug interaction, drug-disease interaction, and not indicated medication) the incorrect dose 42 and route of administration and incorrect rate also take place in mistakes. Conclusion: Intravenous errors can cause significant harm to patients and health-care providers, so proper attention paid to them. Several reasons may cause medication errors such as lack of experience and knowledge of health-care providers, inaccurate communications that do not explain the drug, and the exact dose. The prescribing errors in the medication or dosage were collected, discussed, and clarified so that the risks arising from them observed so that health-care providers and hospital specialists would be alerted and the study would serve as an alarm for health organizations.